Makna dan Nilai Kidung Banyu Pitu pada Upacara Selamatan Memitu di Desa Kedokan Agung Kecamatan Kedokan Bunder Kabupaten Indramayu - Melsya Firtikasari (Nusa Putra University, 2022)
The jurnal discusses about the procedures of performing Kidung Banyu Pitu in the ceremony of Memitu. Kidung Banyu Pitu is one of the traditional arts of the District of Kedokan village, Kedokan Bunder, Indramayu which is sung by a poet. Kidung Banyu Pitu is related to the ceremonial ritual held in every Memitu. Kidung Banyu Pitu is usually done only by one person chanting poet. The chant is not only a plain one, but also is associated with the monotheism sentences. Kidung Banyu Pitu is contained in the Book of Kitab Mustika Rancang; the reflections of the sentence of the Creed (Syahadat). In presenting Kidung Banyu Pitu, the writer found that the forms contain meaningful symbols for the supporters. the meaning of the symbols is very interesting to be observed considering the development of the Indonesian culture, which is leading to the modern society, bringing the changes toward the symbolic culture. Nowadays, the perspective and the attitude of the society tend to begin to shift into a more rational aspects. The society seems to hasitate towards the hidden sacred meanings within the symbols. The writer believes that the form and the meaning of the symbols in Kidung Banyu Pitu in the ceremony of Memitu may reflect the pattern of life of the society in the community where the arts thrive. In other words, the arts of the song in the ceremony of Memitu will be able to describe the daily behaviour of the supporters of the community